2005
DOI: 10.1007/bf02978217
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing dermal matrix regeneration and biomechanical properties of 2nd degree-burn wounds by EGF-impregnated collagen sponge dressing

Abstract: To better define the relationship between dermal regeneration and wound contraction and scar formation, the effects of epidermal growth factor (EGF) loaded in collagen sponge matrix on the fibroblast cell proliferation rate and the dermal mechanical strength were investigated. Collagen sponges with acid-soluble fraction of pig skin were prepared and incorporated with EGF at 0, 4, and 8 microg/1.7 cm2. Dermal fibroblasts were cultured to 80% confluence using DMEM, treated with the samples submerged, and the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…[1][2][3][4] Topical application of several growth factors to the healing impaired wounds could stimulate fibroblast and endothelial cell proliferation, increase the rate and degree of granulating tissue and capillary formation, and thus accelerate wound healing. [5][6][7] Both acidic and basic fibroblast growth factor (aFGF and bFGF or FGF-1 and FGF-2) have many biologic activities including stimulating the proliferation of fibroblasts and capillary endothelial cells, thus promoting angiogenesis and wound healing. [8][9][10][11] We have demonstrated that accelerated healing time was achieved with the topical application of recombinant bovine bFGF (rbbFGF) in patients with second-degree skin burns.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Topical application of several growth factors to the healing impaired wounds could stimulate fibroblast and endothelial cell proliferation, increase the rate and degree of granulating tissue and capillary formation, and thus accelerate wound healing. [5][6][7] Both acidic and basic fibroblast growth factor (aFGF and bFGF or FGF-1 and FGF-2) have many biologic activities including stimulating the proliferation of fibroblasts and capillary endothelial cells, thus promoting angiogenesis and wound healing. [8][9][10][11] We have demonstrated that accelerated healing time was achieved with the topical application of recombinant bovine bFGF (rbbFGF) in patients with second-degree skin burns.…”
Section: Introductionmentioning
confidence: 99%
“…When binding EGFR, EGF could switch on the gene transcription to promote cell division and proliferation of fibroblasts and start further cell migration in wound healing. In the studies of open wounds, it has been proven that EGF can accelerate fibroblast proliferation, contributing to wound healing and scar tissue development [11]. However, there is no basic or clinical research to study the relationship between EGF regulation and pathological scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…Drug release in the wound area can be controlled with particulate system, and this increases the speed of wound healing (Kawaguchi, 2000;Date & Patravale, 2004). In recent studies on micro-/nanoparticulate systems in wound and burn treatment, the use of nitric oxide nanoparticles (Martinez et al, 2009), poly (ethylene-co-vinyl alcohol) nanofiber (Xu et al, 2011), silver nanoparticles (Lakshmana et al, 2010;Xu et al, 2011), fucoidan microparticles (Sezer et al, 2008b), collagen sponges (Still et al, 2003;Lee, 2005), and liposomes containing epidermal growth factor (Alemdaroglu et al, 2008) have examined. Staphylococcus aureus is a gram-positive bacteria, capable of rapidly proliferating in the injured area and causing infection, causes superficial and invasive skin infections.…”
Section: Particulate Systemsmentioning
confidence: 99%
“…The efficacy of microsponges containing epidermal growth factor (EGF) was investigated clinically. It was found that the application of EGF microsponges to the burn surface increased the activity of fibrinogen and thus fibroblast synthesis and migration were seen at the injury site (Lee, 2005). Also, liposome systems in which EGF had been encapsulated was used as particulate carrier systems in the treatment of wounds and burns.…”
Section: Particulate Systemsmentioning
confidence: 99%